Pending Accession to the Palermo Protocol: The Case of Bangladesh - Baiq Wardhani; Farida Noer Fitri (Journal of Islamic World and Politics, 2023)
The People’s Republic of Bangladesh is a Muslim-majority country that has long struggled with human trafficking, and even though Bangladesh is the first largest provider country in human trafficking, especially for sex trafficking, this country needs sixteen years to accede and become part of the Palermo Protocol, which aims to criminalize and punish human trafficking, particularly for women and children. The authors aim to answer why Bangladesh takes so long to access the Palermo Protocol. This study intends to determine the reasons behind Bangladesh’s actions using qualitative-explanatory research, employing the International Regime Theory and the Cost of Sovereignty Theory viewed from a neoliberal perspective. This study uncovered that the reason for Bangladesh acceding to the Palermo Protocol in 2019 was due to three factors: (1) a spike in cases in 2016-2019, (2) Bangladesh’s readiness to fulfill the sovereignty cost of the Palermo Protocol complete in 2019, and (3) Bangladesh’s desire to access advantages under the Palermo Protocol that can help the country to combat the activities of cross-border criminal organizations that perpetuate sex trafficking.